The growth-employment-poverty nexus in Latin America in the 2000s: Bolivia country study - Guillermo Cruces; Gary Fields; David Jaume; Mariana Viollaz (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2015)
During the 2000s Bolivia experienced moderate economic growth and improved all labour market indicators. The economy suffered a slowdown as a consequence of the international crisis of 2008, but Bolivia sustained positive growth rates during that episode. The unemployment rate fell between 2000 and 2012. The composition of employment by occupational groups, occupational positions, economic sectors, and educational levels improved, and the share of registered workers increased. All poverty and inequality indicators decreased substantially between 2000 and 2012. The only negative impact of the international crisis of 2008 was an interruption in the declining trend of unemployment.
Keywords: O15; J01; J30; 330; Bolivia; Latin America; inclusive growth; labour market; poverty